N METODE FUN TEACHING PADA PEMBELAJARAN TEMATIK KELAS V SDN BATUCEPER 1 KOTA TANGERANG - Shindy Rajna Putri; Sa’odah; Rahmawati Eka Saputri (STKIP Subang, 2023)
This study aims to describe the application of the Fun Teaching method to fifth grade Thematic learning at SDN Batuceper 1, Tangerang City. This study uses a qualitative method. The subjects of this study were teachers of class V and students of class V at SDN Batuceper 1. The results of this research were the application of the Fun Teaching method to thematic learning for class V SDN Batuceper 1 Tangerang City going well, because students became more interested in what the teacher conveyed in the process. learning takes place, so that learning can be conveyed properly and increase the activity of students in learning. By using the playing method or learning games, singing, charades and telling stories.